Pilgrimages of Bukhara in the view of academic V.V.Bartold - Бободжонов, Shavkat (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
Orientalist Vasiliy Vladimirovich Bartold became widely known for his works about the history of the East, especially the history of the peoples of Central Asia, and demonstrated his works to the world. From a young age, Bartold was fascinated by the vast Central Asian culture of eight million people (as of the end of the 19th century)